Newspaper Reportage of Cult Related Activities in Emohua Local Government Area of Rivers State - Queen Nneka Alikor (Polit Journal Scientific Journal of Politics, 2023)
The mass media are formidable forces in creating social realities in conflict situations and represent selectively these realities through the process of news framing. Within this context, this study examines newspaper reportage of cult related activities in Emohua Local Government Area of Rivers State. The objectives of the study are to determine the degree of prominence given to the cult related stories in Emohua Local Government Area, and to ascertain how cult related stories are being framed and reported by Nigerian newspapers. The study anchors on the theoretical premise of Media Framing Theory. The study employs quantitative content analysis. The population of this study is limited to the publications of three national newspapers in Nigeria; The Punch, The Guardian and The Nation. The period covered is from June 1st 2021 to April 30th 2022. Within these eleven months, these newspapers had three hundred and thirty five (335) publications apiece making a total of one thousand and five (1005) publications. Purposive sampling was employs while the unit of analysis for this study consisted of news stories, editorials, advertorials, columns/opinions, interviews, feature stories and others focusing on cultism as published by the three newspapers being studied. These newspapers were chosen due to their ownership structure, area of coverage and frequency of publication. The findings reveal that cult related stories were not given prominence as was supposed to be. The study concludes that one challenge that will continue to confront the journalist as well as the media in general is the level of attention to be given to societal violence. The study recommends that newspaper reports should pay more attention to the issue of cultism in Emohua Local Government Area by giving more prominence to it and propel societal action against it.